Complete baby and childcare - Stoppard, Miriam, Dr.; Johon, Jiny; Bagg, Andrea; Vowles, Diana (London : Dorling Kindersley, 2008)
From bathing a newborn to choosing a preschool, in-depth practical advice will give you the confidence to make the best decisions for your child. Case studies give insights on topics including single parenting and dealing with sibling rivalry. Plus find vital first aid guidelines and healthcare advice.
Includes index
Keywords: Child care; Infants care -- Care; Child development; Infants -- Development